ANALISA PENGARUH PENDINGINAN MENGGUNAKAN METODE KRIOGENIK DAN DROMUS COOLANT TERHADAP KEKERASAN DAN KEKASARAN PADA BENDA KERJA DI MESIN BUBUT - Zurianti, Zurianti; Sundari, Ella; Anas, Adian Aristia (MACHINERY Jurnal Teknologi Terapan, 2025)
In this analysis, a quantitative research methodology is used to test which is better the roughness and hardness values of both cryogenic and dromus coolant cooling methods for the manufacture of chuck locks on lathes with AISI 1045 steel material. As well as using the ANOVA analysis method to process the results. And from the results of the measurement using the Surface Roughness Tester roughness test tool carried out, can be concluded that the chuck lock made on a lathe using the cryogenic cooling method has a smaller roughness value, namely at the N7 level, while the dromus coolant method at the N9 level according to the ISO or DIN 4763:1981 roughness standard, which means that the chuck lock that goes through the cooling process with the cryogenic method can produce a smoother surface than the surface that using the Dromus Coolant cooling method. And from Vickers testing can be concluded that cooling with the liquid nitrogen cryogenic method can increase the hardness of the chuck lock with AISI 1045 steel material, namely dromus coolant (10.62%) and cryogenic (14.64%).